Effect Of Pre-Tensioned Level on Axial Stress-Strain Behaviour of Confined Concrete: A Review - Loong Chin, Chee; Khun Ma, Chau; Yang Tan, Jia; Zawawi Awang, Abdullah; Omar, Wahid (International Journal of Engineering and Technology, 2018)
External passive confinement has been used as strengthening scheme to rehabilitate existing reinforced concrete buildings. Passive confinement requires a certain lateral dilation of concrete prior to the activation of the confining effect. Applying pre-tensioned force to the confining material can eliminate the needs of such lateral dilation. This paper presents a review on previous studies conducted about pre-tensioned level in confined concrete. A short discussion is done based on the effect of pre-tensioned level to the three regions of stress-strain curve. It was found that pre-tensioned level affects the stress-strain behaviour of confined concrete. Pre-tensioned level that is too high decreases the strain capacity of the confined concrete. This review suggests that there exists an optimum pre-tensioned level for each confining material.Â Â